Acute toxicity study of Phaleria macrocarpa (Scheff.) Boerl - Azad, Abul Kalam; Wan Sulaiman, Wan Mohd. Azizi; Bakhtiar, M. Taher (2014)

(untitled)
The purpose of this research is to study the antihyperglycemic activity of Phaleria macrocarpa (Scheff.) Boerl. [makotadewa] fruits (mesocarp and pericarp) extracts by STZ-induced sprague-dawley rats model. This research also focused on toxicity study more to evaluate the cytotoxicity and acute oral toxicity by cell line on MCF-7, brine shrimp lethality bioassay and fixed dose (oral feeding, OECD, 425). Phytochemical test showed the presence of alkaloids, carbohydrate, glycosides, saponin, terpene, steroids, phenols and flavonoids. Findings of the present toxicity study suggest that the ethanol extract of PM fruits (mesocarp & pericarp) is non-toxic. In OGTT, the PME at 50, 100 and 200 mg/kg and glibenclamide (0.5 mg/kg) reduced the blood glucose level (hyperglycemia due to glucose load 2 g/kg p.o.) significantly after 2hrs of oral administration, when compared to diabetic control group. On repeated oral administration of PME daily up to 35 days exhibited significant antidiabetic activity in STZ-induced diabetic rats compared with diabetic control. At the end of 35 days of treatment, the dose of 200 mg/kg (PME) was more effective than 100 and 50 mg/kg (PME) and blood glucose level was decreasing from 392.66±3.20 to 174.33±4.32 mg/dl (p˂0.01). On the other hand, at the day of 35, the blood glucose level of normal control, drug control and diabetic control was 132.16±5.79, 134.33±7.18 (p˂0.01), 514.83±7.96. From the results it clearly seen that the blood glucose level trends was decreasing, although it was not became normal. In histology results showed that the pancreases of diabetic control were degranulated and dilated of islet cells whereas drug control showed granulated, nonappearance of dilation and important hyper plasticity of islets. In treatment groups (PME100 and 200 mg/kg) also showed granulated pancreatic islets and prominent hyper plasticity islets. Light micrographs of rat kidney tissue in treatment groups showed various regions of kidneys of treated animals revealed absence of matrix expansion and glomerular basement membrane thickening; suggesting became normal histoarchitecture of renal. Biochemical aspects in treated animals’ all serum analytic parameters were almost similar to drug control group except the treated with 50 mg/kg group. In this way, it may also serve as a good alternative in the present armamentarium of antidiabetic drugs.